TAX REVENUE AND EDUCATION INFRASTRUCTURAL DEVELOPMENT IN NIGERIA - Ernest Oshodin; Osasu Obaretin (Oradea Journal of Business and Economics)
The study examines the effect of tax revenues on education infrastructural development in Nigeria. Tax revenue may be the mainstay of Nigeria’s economy as countries have continually drifted towards a cleaner and friendlier environment. Alternatives to fossil fuel power generation are being explored in countries to reduce the effect of global warming. Also, the continual instability in the price of crude oil in the world market predisposes that tax revenue may likely be a veritable source of funding government expenditure in the future in Nigeria. This study adopted the ex post facto research design to examine the link between tax revenue and education infrastructural development. The education infrastructural development was proxied by the annual allocation to education from 1994 to 2023. Tax revenues were proxied by internally generated revenue through personal income tax, company income tax, petroleum profit tax, tertiary education tax, value-added tax, and customs and excise duties. The error correction model was adopted as the estimation method in this study. These data were sourced from the Nigeria Bureau of Statistic Reports and the Central Bank of Nigeria Statistic Bulletin of the ensuing period. The study revealed a positive and statistically non-significant relationship between personal income tax and education infrastructural development; a negative and statistically non-significant relationship between company income tax, petroleum profit tax, value-added tax, and educational infrastructural development; and a positive and statistically significant relationship between tertiary education tax, customs and excise duty, and education infrastructural development, respectively. The study recommends that more funding from tax generation should be invested in education infrastructures to narrow the gap between the budgetary allocation to education and the 26% recommended by UNESCO. Furthermore, measures should be put in place to enable taxpayers to trace the quantum of tax revenues spent on various infrastructures provided by successive governments in Nigeria. This can go a long way to ensure that political officeholders remain accountable to the taxpayers on the custody of the public resources entrusted to them.